2014
DOI: 10.1007/s00421-014-2893-y
|View full text |Cite
|
Sign up to set email alerts
|

The increase in surface EMG could be a misleading measure of neural adaptation during the early gains in strength

Abstract: The increase in RMS of surface EMG during the early gains in strength should not be directly related to the changes in the neural drive. The relatively small but long-lasting elevated free resting calcium after high-resistance strength training could result in force potentiation and EMG increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
0
20
1
1
Order By: Relevance
“…Traditionally, training-induced increases in EMG amplitude have been interpreted as increases in neural drive to the muscle (Komi et al, 1978; Moritani and deVries, 1979; Hakkinen and Komi, 1983; Thepaut-Mathieu et al, 1988). While caution is warranted when interpreting changes in surface EMG amplitude in this way, normalizing to the M-wave helps to control for peripheral adaptations and/or changes in electrode placement that may influence the EMG signal (Folland and Williams, 2007; Arabadzhiev et al, 2014), allowing EMG QAMP to be considered an indirect indicator of efferent drive (Lepers et al, 2001; Trezise et al, 2016). In combination with the increase in VA, the increase in EMG QAMP observed in the present study seem to reflect greater motor unit excitation following training at 80% 1RM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, training-induced increases in EMG amplitude have been interpreted as increases in neural drive to the muscle (Komi et al, 1978; Moritani and deVries, 1979; Hakkinen and Komi, 1983; Thepaut-Mathieu et al, 1988). While caution is warranted when interpreting changes in surface EMG amplitude in this way, normalizing to the M-wave helps to control for peripheral adaptations and/or changes in electrode placement that may influence the EMG signal (Folland and Williams, 2007; Arabadzhiev et al, 2014), allowing EMG QAMP to be considered an indirect indicator of efferent drive (Lepers et al, 2001; Trezise et al, 2016). In combination with the increase in VA, the increase in EMG QAMP observed in the present study seem to reflect greater motor unit excitation following training at 80% 1RM.…”
Section: Discussionmentioning
confidence: 99%
“…The EMG amplitude was expressed as the root mean square value in μV during the isometric muscle actions. In order to reduce error due to electrode relocation, subcutaneous fat, and the influence of peripheral factors on the EMG signal (Folland and Williams, 2007; Arabadzhiev et al, 2014), the absolute EMG amplitude values during MVIC and at 10–100% of MVIC at Baseline, Week 3, and Week 6 were normalized to the M PP values at Baseline, Week 3, and Week 6, respectively (Behrens et al, 2015) and was thus considered an indicator of central efferent drive to the quadriceps femoris muscles (Lepers et al, 2001; Trezise et al, 2016). Furthermore, EMG amplitude was average across the VL, VM, and RF to calculate quadriceps femoris muscle activation (EMG QAMP ) (Trezise et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Caution should be used when interpreting increases in surface EMG amplitude. Simulation studies have shown that peripheral factors seem to have a larger effect on the gross EMG signal than neural factors (Arabadzhiev et al 2014) and that lower amplitude cancellation could account for an increased EMGrms independent to neural drive (Keenan et al 2006). There is some experimental evidence to suggest that this is possible (Maffiuletti and Martin 2001) due to relatively slow, submaximal load training such as that used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that sEMG should be normalized to the CMAP P‐P amplitude. By subtracting out potential changes within the muscle and technical factors that may vary across test sessions, the remaining sEMG signal should be a true estimate of central drive . Although conceptually appealing, the normalization procedure poses two problems.…”
Section: Discussionmentioning
confidence: 99%
“…By subtracting out potential changes within the muscle and technical factors that may vary across test sessions, the remaining sEMG signal should be a true estimate of central drive. 43,44 Although conceptually appealing, the normalization procedure poses two problems. First, the ratio score combines the measurement error of two variables and can redistribute the variance.…”
Section: Discussionmentioning
confidence: 99%